Edukasi peran vitamin C dalam pencegahan COVID-19 melalui media sosial - Vanda, Geo; Sijabat, Nofitri Dewitasari; Tioline, Naomi Winny; Batubara, Rizka Samira; Letissia, Adela Nadya; Kurniati, Ardesy Melizah; Husin, Syarif; Alkaf, Syifa; Ningsih, Windi Indah Fajar; Anastasia, Monika (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2021)
menyusul